Synthesis, Characterization And Biological Studies Of Substituted Thiadiazine Derivatives And Their Metal Complexes - How, Fiona Ni Foong (2020)
Numerous works have been done to study and investigate thiadiazines and their substituted derivatives. The main reason that initially stirred up researchers’ interest to further pursue these compounds was due to the fact that they are biologically active. A total of twenty compounds were synthesized and characterized successfully. They comprised sixteen substituted thiadiazine derivatives and four metal complexes. The purity of the compounds were determined using thin layer chromatography because most of the compounds are sticky and semi-solid. The compounds were characterized using CHNS analyses, FAAS analyses, FTIR analyses and NMR analyses. Cytotoxic assay was done to determine the cytotoxic activities of the compounds against human colorectal adenocarcinoma cell line, HT29.